Papel do sistema renina angiotensina nas alterações cardiovasculares do diabetes experimental: avaliações "in vivo" e "in vitro" - Malfitano, Christiane [UNIFESP] (2006)
The aim of the present study was to elucidate the role of renin angiotensin system, by “in vivo” and “in vitro” evaluation, on cardiac dysfunction induced by streptozotocin experimental diabetes. Male Wistar rats (250-300g) were divided in 4 groups: control (n=9), control + Enalapril, (n=7, 1mg/Kg), diabetic (n=7, STZ, 50mg/Kg ev), and diabetic + Enalapril (n=7). In vivo studies included: echocardiography as a non invasive tool for ventricular function evaluation and catheterization of left ventricle (LV) to evaluate invasively. The last one was performed in basal condition and after a volume overload protocol. Arterial pressure (AP) was measured directly in awake animals. Biochemistry dosage included angiotensin converting enzyme (ACE) activity in serum, heart and primary cardiac fibroblast culture treated with glucose (25 mM). Diabetes induced hyperglicemia and progressive body weight loss during the protocol. These alterations were not attenuated by enalapril treatment. There were impairment on morphometric (increased LV cavity, reduced intraventricular septum thickness and LV posterior wall thickness) and contractile function parameters (reduced ejection fraction and velocity of circumferential shortening; increased mean E peak velocity, E wave desacceleration time and isovolumetric relaxation time) in the diabetic animalshearts (15 and 30 days). Enalapril treatment attenuated these impairments. In the invasive LF evaluation (30 days), in the basal period, diabetic group presented diminished LV systolic pressure (control: 134 ± 13 vs diabetic 113 ± 14 mmHg*) and LV contractility, measured by +dP/dt (control: 9229 ± 1225 vs diabetic: 6565 ± 1610 mmHg/seg*) and by -dP/dt (control: - 6845± 1002 vs diabetic: - 4745 ± 1557 mmHg/seg*), and also enhanced LV end diastolic pressure (EDP) (control: 4,98 ± 0,98 vs diabetic: 7,36 ± 0,5 mmHg*) as compared to control group. Enalapril treatment did not modify these LV functional parameters in the basal period. Furthermore, the differences observed between control and diabetic groups were maintained after the volume overload protocol. However, enalapril treated diabetic animals presented LV diastolic function parameters (PDF e –dP/dt) after the volume overload similar to their resting values. Differently, the diabetic group showed twice PDF values after volume overload in comparison to it basal PDF values. Direct AP signals measurements (Windaq, 2KHz) in awake animals evidenced hypotension and bradycardia in diabetic groups, treated or not with enalapril, when compared to control groups. Diabetic animals’ serum ACE activity using ZPhe-HHL substrate was 50% increased when compared to control animals; however, enalapril treatment did not inhibit this activity. The opposite was observed in heart tissue: ACE activity reduced 25% in diabetic group and control treated group did not present ACE inhibition in relation to control group. Enalapril treated diabetic group showed ~50% ACE (substrate ZPhe-HHL) inhibition in comparison to treated or untreated control groups. Similar profile was evidenced with ACE substrate HHL in serum and heart. However, it was observed higher ACE substrate ZPhe activation, in both, serum and heart, in comparison to ACE substrate His Leu. Heart ACE protein expression by “western blotting” was increased in diabeticgroups (treated and untreated) in relation to control group with two antibodies: high molecular weight (136KDa) and low molecular weight (69KDa). The increased ACE protein expression was accompanied by heart reduced ACE activity. Glucose treatment increased ~85% ACE activity in primary cardiac fibroblast cultures. In conclusion, streptozotocin experimental diabetes induced impairment in morphometric cardiac parameters and in systolic and diastolic function. Similar condition has been reported in humans. Despite of enalapril therapeutic intervation, in 15 and 30 days, had attenuted these dysfunctions in diabetics, it did not induce AP or heart rate normalization. The inhibition of LV function impairments by enalapril treatment suggests that renin angiotensin system activation plays an important role in the diabetic cardiovascular dysfunctions .